Analisis Kemampuan Guru dalam Membuat Laporan Hasil Belajar Siswa Berbasis Digital di Sekolah Dasar - Khoerunnisa Khoerunnisa; Ibnu Muthi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the ability of elementary school teachers in compiling digital student learning outcome reports, and to identify the factors that influence it. This study was conducted through a library research method by reviewing various scientific articles, books, and empirical reports related to the use of technology in elementary education. The results of the study indicate that teachers' ability in digital reporting is influenced by age, educational background, teaching experience, and involvement in ICT training. The use of reporting applications such as Microsoft Excel, e-Rapor, and Learning Management System (LMS) is still limited, especially in advanced features that actually greatly support reporting efficiency. The main obstacles faced by teachers include lack of ongoing training, limited infrastructure, administrative burden, and mental attitude towards technology. As an improvement strategy, this study recommends tiered technical training, technical guidance at the school level, strengthening learning communities such as KKG and MGMP, and integration of ICT training in the Continuous Professional Development (PKB) program. This research is expected to be the basis for making policies that are more adaptive to the needs of teachers in the digital era.